2014
DOI: 10.1007/s00415-014-7281-3
|View full text |Cite
|
Sign up to set email alerts
|

Etoposide/carboplatin chemotherapy for the treatment of metastatic myxomatous cerebral aneurysms

Abstract: (2014). Etoposide/carboplatin chemotherapy for the treatment of metastatic myxomatous cerebral aneurysms. Journal of Neurology, 261(4):828-830.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
0
11
0
1
Order By: Relevance
“…38 Another method that is still controversial is to treat enlarging aneurysms, which are not good candidates for surgical or endovascular treatment, with chemotherapeutics to stabilize the lesions. 44…”
Section: Discussionmentioning
confidence: 99%
“…38 Another method that is still controversial is to treat enlarging aneurysms, which are not good candidates for surgical or endovascular treatment, with chemotherapeutics to stabilize the lesions. 44…”
Section: Discussionmentioning
confidence: 99%
“…The results from chemotherapy have been equivocal (31), but evidence has shown that the combination of radiotherapy and chemotherapy is useful for the treatment of myxo ma metastasis, thereby reducing the likelihood of formation of myxomatous aneurysms (32)(33)(34). Other investigators have suggested that despite independent reports of microsurgical resection/endovascular intervention, chemotherapy, and radiotherapy for the treatment of cardiac myxomatous intracranial aneurysms, there is still a lack of clear guidelines (35). In this case, the presence of intracranial aneurysm associated with cardiac myxomatosis and a small amount of bleeding from the left middle cerebral artery aneurysm suggested that there might be irreversible damage to the artery wall structure.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the fusiform shape, coil embolization with stenting could be necessary 7) . There remains much debate regarding the possibility that chemotherapeutics can stabilize myxomatous aneurysms when surgery or endovascular procedure is not possible 3) . In conclusion, our case shows that surgical resection with bypass surgery is a useful option for the treatment of cerebral myxomatous aneurysms.…”
Section: Discussionmentioning
confidence: 99%